Problematika Pendidikan Islam di Era Otonomi Daerah - Upik Khoirul Abidin (Journal of Education and Religious Studies, 2022)
Education is the most important element in building a nation, even often said the progress of a nation can be seen from how good the quality of education in the country. Therefore, it can be said that between education and the State influence each other. For example, in Indonesia, the role of the government is very large in determining the quality of education, if the quality of education in Indonesia is good, it will bring progress to the nation. So, it has become imperative for the Government to continue to make efforts to improve the quality of education, starting from improving the curriculum, learning strategies, even to the level of policy (the enactment of Regional Autonomy) where education is the responsibility of the central government (centralistic) then turns to the authority of the Regional Government of Provinces, Districts / Municipalities is very influential (decentralist). This paper will discuss more deeply the third point of one of the efforts to improve the quality of education mentioned above. Whether this decentralization policy is the best solution in education or still leaves various problems, and more where are the positive values between centralization and decentralization towards improving the quality of education in Indonesia.